Design of a Leg Lift Aid Device Used in Bed for the Elderly - Jiachao Luo; Qunbiao Wu; Baole Zhao; Qinhu Sun; Haina Yang; Yuyan Zhang (Jixie chuandong)
In order to solve difficulties of going to bed and getting up for the elderly，a device is designed to assist them in going to bed. The track of the elderly's leg going to bed is analyzed. Based on mathematical modeling，the leg lift trajectory is simulated by intersection curves between spherical surface and conical surface，a spatial linkage is designed to help leg lift and its specific structure design and motion simulation are analyzed. The simulation results show that the device can realize leg lift trajectory and run smoothly，the theoretical feasibility is verified. The physical construction and practical test are carried out，it is proved that the device has clever mechanism and compact structure and can realize auxiliary leg lift，can be adapted to different bed types and has a broad application prospect.